2023
DOI: 10.3389/fmats.2022.1059184
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology and COVID-19: Prevention, diagnosis, vaccine, and treatment strategies

Abstract: In December 2019, Coronavirus pandemic (COVID-19) caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) viruses, which affected the whole world, is emerged. The details on the epidemiology, infection source, transmission mode, and prognosis of SARS-CoV-2 gave in this review. Universal infection control standards such as hand hygiene, environmental cleanliness, use of personal protective equipment, and quarantine used to prevent the spread of COVID-19 without vaccine. However, many vaccine cand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 259 publications
0
1
0
Order By: Relevance
“…Only when herd immunity develops, as a result of an efficient vaccination or if the population has already been exposed and is resistant to reinfection, will COVID-19 be suppressible. Until there is a successful vaccination, there is almost little hope of a return to pre-COVID-19 social behavior [66,68]. Antiviral drugs and other sorts of drugs that prevent viral replication may be delivered via nanotechnology.…”
Section: ■ Nanomaterials For Subunit Dna and Rna Covid-19 Vaccinementioning
confidence: 99%
“…Only when herd immunity develops, as a result of an efficient vaccination or if the population has already been exposed and is resistant to reinfection, will COVID-19 be suppressible. Until there is a successful vaccination, there is almost little hope of a return to pre-COVID-19 social behavior [66,68]. Antiviral drugs and other sorts of drugs that prevent viral replication may be delivered via nanotechnology.…”
Section: ■ Nanomaterials For Subunit Dna and Rna Covid-19 Vaccinementioning
confidence: 99%
“…Angiotensin-converting enzyme 2 (ACE2) receptors allow COVID-19 viruses to enter cells, so lowering ACE2 levels could help cut down on the number of infections. It was suggested that using nanotechnology in the gloves to catch the viruses before they enter the cells would be very beneficial [ 4 ].…”
Section: Reviewmentioning
confidence: 99%
“…The vaccines have been developed and tested at an unprecedented pace, thanks to advancements in biomedical science. This has been a significant achievement, and it provides hope for the control of other infectious diseases in the future [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The genomic structure of the SARS-CoV-2 virus has been found to have a 79.5% match with the SARS-CoV-1 virus which was the causative agent of an epidemic in the year 2002 [3,4]. In addition, the SARS-CoV-2 virus exhibits a 96% genome similarity to RaTG13 which is a species of a bat coronavirus [3,4,6]. As validated by evolutionary research and due to the genomic similarity, the bat is now considered to be the main biological host of SARS-CoV-2 virus.…”
Section: Introductionmentioning
confidence: 98%
“…As validated by evolutionary research and due to the genomic similarity, the bat is now considered to be the main biological host of SARS-CoV-2 virus. In order to successfully prevent and manage COVID-19 infections, there is need to understand it's viral protein structure as well as the links between its functions and the interactions with the human host machinery during pathogenesis [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%